THE EFFECT OF HAND DRYERS ON RESTROOM INDOOR AIR QUALITY (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The widespread use of hand-dryers in public restrooms raises concerns about hygiene and indoor air quality. Hand-dryers facilitate microbial proliferation and aerosolization, increasing infection risk and degrading indoor air quality by dispersing pathogens and allergens. This study investigates microbial growth and air contamination, advancing the field by exploring factors such as humidity, airflow mechanics, and particle count concerning various hand-dryer types. Different models of 8 warm air dryers and 2 jet dryers in ten restrooms were sampled (4 female, 4 male and 2 accessible) in an academic institution. The study involved air sampling from the hand-dryer outlet for 30 seconds directly onto agar plates and surrounding air sampling using the “SAS SUPER ISO 180” device. Microbiological samples were then cultivated on different media, manually counted and identified. Fungi were identified by native smears and safranin staining, bacteria using VITEK. Particle count was measured before and during hand dryer use with “TSI P-TRAK”, while other variables such as room temperature, humidity, CO2 levels, hand dryer air flow velocity, temperature were also recorded. The data was processed using IBM SPSS. Statistically significant correlations were found: airflow temperature negatively correlated with fungal dispersal on Sabouraud agar (r=-0.747, p<0.05), CO₂ positively correlated with bacterial dispersal on Trypticase soy agar (TSA) (r=0.661, p<0.05), and humidity showed a significant positive correlation with TSA CFU/min (r=0.636, p<0.05). Microbial contamination was detected in all restrooms. Warm air dryers consistently emitted higher bacterial loads than jet dryers across all tested media. Hand-dryer air ranged from 0 to 1360 CFU/min, while restroom air ranged from 0 to 1424 CFU/m3. Most fungi identified were molds (Mucor spp., Penicillium spp., Aspergillus spp.), with 22 yeast colonies. Analysis identified various opportunistic and pathogenic bacteria, including Acinetobacter baumannii, Escherichia coli, Staphylococcus and other species. Average particles count before use was 7831, while during use 11668. The findings indicate that while hand dryers may contribute to bacterial and fungal dispersal, factors such as airflow temperature, humidity, and CO2 levels also play significant roles in microbial behavior.